The origins and development of the notion of isostheneia in Greek scepticism: A collection of texts. - Desjardins, Michael. (University of Ottawa (Canada), 1996)
The research collected texts in which ancient authors wrote of issues having to do with the sceptical notion of isostheneia. The collection finds its beginnings under the auspices of Calliope, the muse of fine speaking, and in the tendency to produce accounts in antithetical terms or in opposition to one another. In the Classical period anticipations of the development of the notion are found in the thinking of the physicists and the speculation of the physicians. Most significant for the development of the notion seems to have been the emergence of some of the differences between rhetoric and dialectic, the one elaborated under the pressure of the practice of the Sophists and Isocrates, the other isolated by Socrates and detailed by Plato as a philosophical method. The medical communities seem to have produced a paradigm of balance between opposed elements as the foundation of vitality and health. At the end of the Classical period, Aristotle appears to have provided some model for the sceptical notion in his practice of arguing in utramque partem, and to have anticipated it in his description of perplexity. Both Plato and Aristotle were familiar with some of the modes which were later collected by Aenesidemus. In the Hellenistic period it appears to have been in the ad hominen argument of Arcesilaus that the sceptical notion first became articulate as the basis of suspension of judgment. With Carneades the practice of arguing both for and against any proposition and relying heavily on rhetoric appears to have been the model on which the sceptical way was being fashioned. A controversy between Epicureans and Stoics over how to decide between acts of assent founded on equally reliable sense perceptions is suspected to be at the basis of the articulation of the notion of isostheneia. In the Hellenistic period the development of the notion seems also to have been assisted by the requirement for some therapeutical intervention by means of which health might be restored. With the Imperial period the sceptical notion first became apparent in the literature: Greek words from the root $\iota\sigma\sigma\sigma\theta\epsilon\nu$--which would be later used to name it seem to have begun to find their way into texts from its beginning. Some evidence is introduced to indicate that Philo Judaeus had knowledge of the subject of this study. By the time that Plutarch wrote Adversus Colotem the notion had become fully articulate. Later in the second century authors of the second sophistic also appear to have been comfortable with the notion at the basis of the sceptical way. Galen used the word on many occasions to describe anatomical and physiological details and a passage is included to indicate that he had knowledge of the notion. Sextus Empiricus compiled the arguments of the Pyrrhonians sometime around the end of the second century, and used words from the root $\iota\sigma\sigma\sigma\theta\epsilon\nu$--to identify the notion. Late in the Imperial period and reflecting what was to occur in the Medieval Latin west, Augustine seems to have been unaware that the equal persuasiveness of incompatible accounts was the basis for withholding assent. In the Greek east the notion continued to appear in some literature produced after the end of the texts known as ancient philosophy.
Keywords: Philosophy.